OS CENTROS DE ATENÇÃO PSICOSSOCIAL – CAPS – DE PONTA GROSSA/PR PELO OLHAR DOS USUÁRIOS, FAMILIARES E TRABALHADORES - Orlowski, Viviane Matoski (2015)
This study analyzes the perceptions of workers, users, and their families on the Psychosocial Attention Centers (CAPS) of Ponta Grossa. We present the services offered, the actions carried out in these spaces, the expectations of CAPS users, the working conditions of the professionals (work regulations, workload hours, organizational environment, and qualification), and the influence of these factors on the quality of actions and on the daily work routine. Throughout this research, we had access to the dossier “Ponta Grossa – Saúde Mental”, from Associação de Apoio aos Portadores de Distúrbios de Ordem Mental (attachment B), forwarded to the Department of Public Prosecution of Paraná in March 2014. The dossier requires the compliance with the National Politics of Mental Health, showing that the components of the city's Psychosocial Attention Network (RAPS) are not in accordance with what is legally recommended. Even that the information from the dossier demonstrate the precariousness of the psychosocial attention network in Ponta Grossa, it is relevant to know the contributions that CAPS are carrying out in the lives of the supported population, according to the opinions of workers, users, and their families. This is an exploratory study with qualitative approach, bibliographical research, and documentary research. The following procedures were used for the collection of data: interviews, questionnaires, and observation; a methodological triangulation that assisted the understanding and analysis of our data. The research universe are the three CAPS of Ponta Grossa: CAPSad - alcohol and drugs, CAPSi - children, and CAPS II - mental disorder. As sample, we selected subjects amongst the ones that attend CAPS, their families, and professionals from the assistance teams. Interviews with the Management of Mental Health of Ponta Grossa and with CAPS coordinators have also been carried out. Two questionnaires have been applied to the users, two to their families and one for the workers of the three CAPS. This work is divided in three chapters. The first one explains the research's methodological path, a qualitative, descriptive, exploratory study using triangulation methods, what allowed the contextualization of the subject. In chapter 2, historical aspects on the Brazilian Psychiatric Reform's route are discussed, and the conception of health services network are analyzed, emphasizing the Psychosocial Attention Network and the Psychosocial Attention Centers. The third chapter contextualizes the Psychosocial Attention Centers of Ponta Grossa (for understanding of its administrative reality and diagnosis of the physical and structural conditions of the establishments). It also presents the profile of CAPS's workers and the results of the questionnaires applied to the research subjects.